2022
DOI: 10.1186/s12974-022-02602-y
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of STING signalling in CNS injury: inflammation, autophagy, necroptosis, ferroptosis and pyroptosis

Abstract: Stimulator of interferons genes (STING), which is crucial for the secretion of type I interferons and proinflammatory cytokines in response to cytosolic nucleic acids, plays a key role in the innate immune system. Studies have revealed the participation of the STING pathway in unregulated inflammatory processes, traumatic brain injury (TBI), spinal cord injury (SCI), subarachnoid haemorrhage (SAH) and hypoxic–ischaemic encephalopathy (HIE). STING signalling is markedly increased in CNS injury, and STING agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 144 publications
0
42
0
Order By: Relevance
“… 65 However, STING signalling plays a crucial role in numerous forms of cell death, including ferroptosis. 66 , 67 Moreover, co-immunoprecipitation studies demonstrated that STING could interact with the TAK1 protein, indicating an interaction between STING and TAK1. 68 However, the relationship between STING expression and TAK1 expression in human diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 65 However, STING signalling plays a crucial role in numerous forms of cell death, including ferroptosis. 66 , 67 Moreover, co-immunoprecipitation studies demonstrated that STING could interact with the TAK1 protein, indicating an interaction between STING and TAK1. 68 However, the relationship between STING expression and TAK1 expression in human diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cytosolic immunogenic nucleic acids sensing, for instance cGAS–STING pathway, has been increasingly recognized as a primary determinant and potent regulator in neuroimmunological diseases, neurological infections, neurodegenerative diseases, as well as neuro-oncology [ 46 51 ]. Endoplasmic reticulum protein STING can be bound and activated by cytosolic nucleic acids sensor cGAS, and then lead to a complex intracellular signaling cascade and nuclear translocation of transcription factors, such as NF-κB, that stimulate the production of various pro-inflammatory molecules, including cytokines, chemokines, type I interferons (IFNs) [ 52 , 53 ]. Previous studies have observed the activation of microglial cGAS–STING pathway in exogenous viral infections, traumatic brain injury, cerebral ischemic stroke, and Alzheimer's disease [ 50 , 54 57 ], however, the activators of cGAS–STING pathway were come from exogenous virus or extracellular nucleic acids released by damaged or dead cells that phagocytized by microglia.…”
Section: Discussionmentioning
confidence: 99%
“… Wang et al (2012) reported that a small amount of autophagy exists in normal brain neurons; however, it is activated in large quantities after SAH. Autophagy can improve cerebral oedema, protect the blood-brain barrier, reduce cortical neuronal apoptosis and improve clinical prognosis after intervention with rapamycin (RAP) and 3-methyladenine (3-MA) ( Hu X. et al, 2022 ; Pang et al, 2022 ). Lu et al reported that melatonin enhances autophagy in brain vessel endothelial cells, then protect blood-brain barrier integrity.…”
Section: Neuronal Autophagymentioning
confidence: 99%